$$\lim_{n \to \infty}\left(n^{1\over n}+{1\over n}\right)^{n\over \ln n}$$

The limit is same as

$$e^{\displaystyle{\lim_{n \to \infty}}{n^{(1+{1\over n})}-n+1\over \ln n}}$$

But I am stuck here , I noticed that if I take $n$ common from the numerator then it is of the form $0 \times \infty$ , but I can't seem to solve further , using L'hopital's rule is too hectic or perhaps not meant to solve this one . I couldn't use any of the Maclaurin expansions either in this case .

Could someone please guide me in this ?

Thanks !

  • 3
    $\begingroup$ Hint. You may write $$\left(n^{\frac{1}{n}}+\frac{1}{n}\right)^{\frac{n}{\log n}}=\exp\left( 1 + \frac{n}{\log n}\log\left(1+\frac{1}{n^{1+1/n}}\right)\right). $$ $\endgroup$ – Sangchul Lee Jun 30 '20 at 4:49
  • 1
    $\begingroup$ Take $\log$ sides and note that $\lim n^{\frac{1}{n}}$ is same as $\lim n^{\frac{1}{n}} +\frac{1}{n}$ $\endgroup$ – Hrishabh Jun 30 '20 at 4:53
  • $\begingroup$ @Hrishabh that was great , it got solved without even using the pen , thanks ! $\endgroup$ – ARROW Jun 30 '20 at 5:31

Here is simple approach for this limit. $$ \lim_{n\to \infty} \left(\sqrt[n]{n} +\frac{1}{n} \right)^{\frac{n}{\ln n}} = \lim_{n\to\infty} \left[ n^{\frac{1}{\ln n}}\left(1+\frac{1}{n \sqrt[n]{n}}\right)^{\frac{n}{\ln n}}\right]=\lim_{n\to\infty} n^{\frac{1}{\ln n}} \exp\left(\lim_{n\to\infty} \frac{1}{\sqrt[n]{n} \ln n}\right) =e \times 1 = e $$ Since $$ \lim_{n\to\infty} n^{\frac{1}{\ln n}} = \exp\left(\lim_{n\to \infty} \frac{\ln n}{\ln n}\right)=e$$

In the latter limit we use the fact that $\displaystyle \sqrt[n]{n} =1$ so as $n\to \infty $ and $\ln n\to \infty$ which tell us that $\frac{1}{\sqrt[n]{n} \ln n}$ is decreasing sequence for all $ n>1$ and it's limit around large $ n$ is $\displaystyle \lim_{n\to\infty}\frac{1}{\ln n} =0$ .

  • $\begingroup$ I think that $\sqrt[n]{n}$ should be in the denominator in the last step .(right before $e \times 1$ ) $\endgroup$ – ARROW Jun 30 '20 at 5:37
  • $\begingroup$ @ARROW, its typo. I have fixed it. Thank you for pointing out. :) $\endgroup$ – Naren Jun 30 '20 at 5:45

$$a_n=\left(n^{1\over n}+{1\over n}\right)^{n\over \log( n)}\implies \log(a_n)={n\over \log( n)}\log\left(n^{1\over n}+{1\over n}\right)$$ By Taylor $$\log\left(n^{1\over n}+{1\over n}\right)=\frac{\log (n)+1}{n}-\frac{2\log (n)+1}{2n^2}+O\left(\frac{1}{n^3}\right)$$ $$\log(a_n)=1+\frac 1 {\log(n)}-\frac{2\log (n)+1}{2n\log(n)}+O\left(\frac{1}{n^2}\right)$$ $$a_n=e^{\log(a_n)}=e \, \exp\left(\frac 1 {\log(n)}-\frac{2\log (n)+1}{2n\log(n)}+O\left(\frac{1}{n^2}\right) \right)$$ xhish shows the limit and how it is approached.

Moreover, this gives you a shortcut method for an estimate of $a_n$. Suppose $n=10$; the truncated expression would give $3.716$ while the exact value is $3.788$.

It would give a relative error lower than $1$% for $n \geq 15$ and lower than $0.1$% for $n \geq 54$.


Your first step is correct, as in taking the exponential and the logarithm.

However, the next quantity is not correct. Take $L$ to be the limit in question, then

$$L=\exp\left(\lim_{n\to\infty}\frac{n}{\log n}\log\left(n^{\frac1n}+\frac1n\right)\right).$$ I can't quite piece how did you get to your quantity but that's beside the point. Now rewrite $$\frac1n=n^{-1+\left(\frac1n-\frac1n\right)}=n^{\frac1n}\cdot n^{-\left(1+\frac1n\right)}.$$ Using the product rule for logarithms, the $\log$ right there becomes

$$\log\left(n^{\frac1n}+\frac1n\right)=\log\left(n^{\frac1n}+n^{\frac1n}\cdot n^{-\left(1+\frac1n\right)}\right)=\frac{\log n}n+\log\left(1+n^{-\left(1+\frac1n\right)}\right).$$ Back in the original expression we substitute back to get \begin{align*} L&=\exp\left(\lim_{n\to\infty}\frac{n}{\log n}\left(\frac{\log n}n+\log\left(1+n^{-\left(1+\frac1n\right)}\right)\right)\right)\\ &=\exp\left(1+\lim_{n\to\infty}\frac{n}{\log n}\cdot\log\left(1+n^{-\left(1+\frac1n\right)}\right)\right). \end{align*}

We now treat the last logarithm, so as an strategy, we know that $\frac{n}{\log n}$ goes to $\infty$ as $n$ grows since $n\gg\log n$. Therefore its inverse goes to zero, then we would like the other quantity to go to zero as well to apply L'Hôpital's rule. It is enough to show that $n^{-\left(1+\frac1n\right)}$ tends to zero as $n$ grows.


However, I feel that trying to apply L'Hôpital's rule here would be too convoluted. If anyone is willing to expand on this procedure I would be grateful.

I'll be back once I see how to get around this.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.